2020
DOI: 10.1021/acs.macromol.0c00431
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Gradient Copolymers Composed of Norbornene and Higher α-Olefins Using an ansa-Fluorenylamidodimethyltitanium-[Ph3C][B(C6F5)4] Catalyst System

Abstract: The copolymerization of norbornene (NB) and various α-olefins [1-octene (O), 1-decene (De), and 1-dodecene (Do)] was achieved with high activity using ( t BuNSiMe2Flu)­TiMe2 (1)-[Ph3C]­[B­(C6F5)4] and 2,6-bis­(1,1-dimethylethyl)-4-methylphenol (BHT)-treated tri-i-butylaluminum ( i Bu3Al) or tri-n-octylaluminum (Oct3Al) as a scavenger. The catalytic systems gave NB/α-olefin copolymers with number-average molecular weights over 100,000 and polydispersity indices below 1.3. The copolymers possessed the gradient s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…The strain−stress curves of these copolymers dramatically changed from brittle to ductile behaviors with the increasing length of the alkyl group of αolefin. 28 Interestingly, T g values at very low temperatures from −46.8 to −11.1 °C were observed for these copolymers due to the gradient structure that has an α-olefin rich segment. On the other hand, Ihm et al showed the vinyl-addition copolymerization of NB/5-n-alkyl-2-NB using palladium catalysts, where the synthesized copolymers have tunable high T g values of 161−285 °C depending on the length of the alkyl chains.…”
Section: ■ Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The strain−stress curves of these copolymers dramatically changed from brittle to ductile behaviors with the increasing length of the alkyl group of αolefin. 28 Interestingly, T g values at very low temperatures from −46.8 to −11.1 °C were observed for these copolymers due to the gradient structure that has an α-olefin rich segment. On the other hand, Ihm et al showed the vinyl-addition copolymerization of NB/5-n-alkyl-2-NB using palladium catalysts, where the synthesized copolymers have tunable high T g values of 161−285 °C depending on the length of the alkyl chains.…”
Section: ■ Introductionmentioning
confidence: 88%
“…Recently, Shiono et al reported the studies for the copolymerization of NB and various α-olefins such as 1-octene, 1-decene, and 1-dodecene using titanocene-based catalysts to investigate the physical properties of COCs depending on the combination and composition of the comonomers and the sequence distribution. , NB/α-olefin copolymers with the gradient structure composed of an NB-rich segment and an α-olefin-rich terminal were produced. The strain–stress curves of these copolymers dramatically changed from brittle to ductile behaviors with the increasing length of the alkyl group of α-olefin . Interestingly, T g values at very low temperatures from −46.8 to −11.1 °C were observed for these copolymers due to the gradient structure that has an α-olefin rich segment.…”
Section: Introductionmentioning
confidence: 99%
“…This catalyst system promotes living copolymerization of NB and various α-olefins at room temperature with a small amount of a suitable scavenger such as OctAl(BHT) 2 . 28 All the comonomers 3a−d gave copolymers in high yield after the reaction for 1 h under this condition (run 1−4). The molecular weight of all these copolymers reached up to 10 4 orders, but the copolymers of 3a−3c showed a broad molecular weight distribution (D̵ > 2) despite the use of a single-site catalyst.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…prepared gradient COCs of norbornene with α ‐olefin including 1‐octene, 1‐decene, and 1‐dodecene instead of ethylene or propylene by using ( t ‐BuNMe 2 SiFlu)TiMe 2 / [Ph 3 C][B(C 6 F 5 ) 4 ]. [ 4,50‐51 ] It was found that the elongation at break of NBE/ α ‐olefin copolymers was enhanced with the increase of alkyl group length of α ‐olefin, however, their tensile strength was simultaneously decreased. The elongation at break of NBE/1‐dodecene copolymer reaches 22%, but its tensile strength is only 5 MPa, T g of the material was also greatly decreased.…”
Section: Background and Originality Contentmentioning
confidence: 99%